Hubungan Pengetahuan Dan Paritas Ibu Dengan Pemberian Makanan Prelakteal Di Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang 2023 - Marta Armita Silaban; Damayanty S; Ika Damayanti Sipayung; Anggun Lestari (STIKes Ibnu Sina Ajibarang, 2023)
Prelakteal foods are foods and beverages given to infants in the first days after birth before breast milk is released. The percentage of infants in Indonesia who gave prelakteal food by province was 44.3%. The purpose of this study was to determine the relationship of knowledge and parity with prelakteal food delivery in infants in the working area of ​​ Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2023. This type of research is an analytic survey with Cross Sectional approach. The study population of all mothers with infants aged 0-6 months were 57 respondents, and samples using saturated samples. The result of statistical test using chi square test, obtained the calculation of the value of p value of knowledge (0.002) and <α = 0.05, it means there is a relationship of mother knowledge with prelakteal feeding to infant in Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2023. And statistic test result parity variables obtained results p value (0.008) and <0.05, it means there is a relationship Parity Mother With Prelakteal Food Provision In Babies in Desa Bangun Rejo Kecamatan Tanjung Morawa Kabupaten Deli Serdang Tahun 2023.